(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article covers analysis of the force interaction of knife and material being cut; the components of cutting force on the main operating elements of cutting tool are obtained. The mathematical analysis of the value of “clean” cutting component is given, and the cutting ability of the blade with purpose of improving the cut quality is determined.